2021
DOI: 10.1101/2021.04.27.438445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Stable Nano-Vaccine for the Targeted Delivery of Tumor-Associated Glycopeptide Antigens

Abstract: We have developed a novel antigen delivery system based on polysaccharide-coated gold nanoparticles (AuNPs) targeted to antigen presenting cells (APCs) expressing Dectin-1. AuNPs were synthesized de-novo using yeast-derived beta-1,3-glucans (B13Gs) as the reductant and passivating agent in a microwave-catalyzed procedure yielding highly uniform and serum-stable particles. These were further functionalized with both peptides and glycopeptides from the tandem repeat sequence of mucin 4 (MUC4), a glycoprotein ove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Many carriers have been investigated, such as nanomaterials, 7 liposomes and proteoliposomes, 8 polysaccharides, 9 dendrimers, 10 and immunogenic proteins including keyhole limpet hemocyanin (KLH), 11,12 tetanus toxoid (TT), 13 and cross reactive material-197 (CRM-197). 14,15 KLH, 16 a large glycoprotein, is the most advanced carrier for cancer vaccine studies, as multiple KLH-TACA conjugates have been evaluated in late-stage clinical trials.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many carriers have been investigated, such as nanomaterials, 7 liposomes and proteoliposomes, 8 polysaccharides, 9 dendrimers, 10 and immunogenic proteins including keyhole limpet hemocyanin (KLH), 11,12 tetanus toxoid (TT), 13 and cross reactive material-197 (CRM-197). 14,15 KLH, 16 a large glycoprotein, is the most advanced carrier for cancer vaccine studies, as multiple KLH-TACA conjugates have been evaluated in late-stage clinical trials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As TACAs alone cannot generate effective anticancer immune responses, carriers are critical for TACA-based vaccine design. Many carriers have been investigated, such as nanomaterials, liposomes and proteoliposomes, polysaccharides, dendrimers, and immunogenic proteins including keyhole limpet hemocyanin (KLH), , tetanus toxoid (TT), and cross reactive material-197 (CRM-197). , KLH, a large glycoprotein, is the most advanced carrier for cancer vaccine studies, as multiple KLH-TACA conjugates have been evaluated in late-stage clinical trials. , Clinical studies have shown that cancer patients capable of producing high levels of anti-TACA antibodies following KLH-TACA immunization are associated with better prognosis and survival. , However, for the full patient cohort, vaccination failed to exhibit statistically significant protection , highlighting the critical need to improve levels of anti-TACA antibodies produced.…”
Section: Introductionmentioning
confidence: 99%